Tear-out coupling and water line - DUNCAN SCOTT (2009)
A unitary removable barrier for installation in a cylindrical water line to selectively block the water line to passage of water therethrough. The unitary removable barrier is composed of a single piece rubber body having at least one cylindrical section sized to receive upstream and downstream pipes of the water line. A unitary rubber planar disc molded with the cylindrical section is of a circular circumference and which completely blocks the water line but which is selectively removable from the cylindrical section thus removing the barrier to the passage of the waste through the line.